Giant solitary hydatid cyst of spleen—A case report - Pukar, M.M. (Elsevier, 2013)
INTRODUCTION: Primary hydatid disease of the spleen is very rare and even rarer to cause (any complication … pancreatitis.). Usually, splenic hydatid cysts are secondary, either resulting from spontaneous spread of cysts or occurring after operations involving hydatidosis in other regions. Here, we report a case of a primary isolated splenic hydatid cyst treated with a classical surgical approach. This case report and literature review describes the management of hydatid splenic invasion. PRESENTATION OF CASE: We report the case of a 28-year-old female who presented with left hypochondriac non tender swelling/(mass). Abdominal ultrasonography and computed tomography (CT) revealed a cyst located in the spleen. The diagnosis was confirmed by a serological test. Surgical treatment involved a radical en bloc splenic resection (together with resection of the diaphragm and subcutaneous tissue.) The postoperative course was uneventful with three weeks of albendazole treatment. CT follow-up at six months demonstrated the absence of recurrence. Histopathologic examination revealed a hydatid cyst. DISCUSSION: Complete aggressive surgical en bloc resection resection is the gold standard treatment of patients with hydatid cysts with the aim to remove all parasitic and pericystic tissues. CONCLUSION: The infrequency with which it is encountered makes splenic hydatid disease a formidable early diagnostic challenge especially in nonendemic areas. Hydatid disease should be considered in the differential diagnosis of all cystic masses in the spleen/(abdomen), especially in the geographical regions where the disease is endemic.